The relationship between the cyberbullying/cybervictmization and loneliness among adolescents - Sahin, Mustafa (Children and youth services review, 2012)
This study focuses on the relationship between the concepts of cyberbullying/cybervictimization and loneliness. The subjects of the study were 389 secondary school students, of whom 159 were boys and 230 were girls, from various schools in the city of Trabzon. The study was carried out in the fall semester of the 2009–2010 academic year. The Loneliness Scale (UCLA) and the Cyberbullying Scale were used in the study. Correlation technique, multiple regression analysis and independent t test, were employed for statistical analysis. The study concluded that there was a significant correlation between becoming a cybervictim and loneliness among adolescents. Loneliness predicted by cybervictimization. These results were discussed and some conclusions were made. ► Any relationship between loneliness and cyberbullying/cybervictimization. ► A significant correlation was found between cybervictimization and loneliness. ► There was no significant correlation between cyberbullying and loneliness.